2011
DOI: 10.1186/1476-7120-9-27
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exercise training on left ventricular function in young elite athletes

Abstract: BackgroundRegular training, in particular endurance exercise, induces structural myocardial adaptation, so-called "athlete's heart". In addition to the 2D standard echo parameters, assessment of myocardial function is currently possible by deformation parameters (strain, rotation and twist). Aim of study is to assess the role of rotation and twist parameters for better characterize the heart performance in trained elite young athletes from different kind of sports. Eventually, verify early on any possible impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 26 publications
2
19
0
5
Order By: Relevance
“…Our findings are consistent with these studies showing that long term IEET increases the LV strain without changing the EF. In a case-control study, De Luca et al (19) reported, using layer specific analysis, that epicardial strain was higher and endocardial strain was comparable in young cyclists in comparison with the control group. In contrast to this study, the present study, which featured longitudinal follow-up, did not include layer specific analysis.…”
Section: Left Ventricular Systolic Functions and Left Ventricular Strainmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with these studies showing that long term IEET increases the LV strain without changing the EF. In a case-control study, De Luca et al (19) reported, using layer specific analysis, that epicardial strain was higher and endocardial strain was comparable in young cyclists in comparison with the control group. In contrast to this study, the present study, which featured longitudinal follow-up, did not include layer specific analysis.…”
Section: Left Ventricular Systolic Functions and Left Ventricular Strainmentioning
confidence: 99%
“…Besides, 2D strain imaging may help in the understanding of the structural changes related to the athletes' heart. A study by De Luca et al (19) revealed that LV apical twist improved in young athletes after exercise training. However, Chan-Dewar et al (20) found LV twist comparable.…”
Section: Introductionmentioning
confidence: 99%
“…Several pathophysiologic mechanisms have been suggested, nevertheless there is paucity of clinical markers that can characterize a hemodynamic milieu predictive of the risk of cardiac remodeling either following infarction (Nijveldt et al, 2009;Wu et al, 2008) or excessive sport activity (De Luca et al, 2011;Mihl et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Спортсменов рассматривают как отдельную группу людей, ведущих уникальный образ жизни и способных к экстраординарным физическим достижениям [1,2]. Однако, ресурсы человеческого организма не безграничны, даже если речь идет о профессиональных атлетах [3].…”
unclassified
“…Предпатологические и патологические состояния миокарда, связанные с активной тренировочной и соревновательной деятельностью, проявляются как в процессе спортивной карьеры, так и после ее окончания [10]. Иногда отмечаются противоречивые данные в интерпретации особенностей физиологических и патологических изменений сердечной мышцы у лиц, занимающихся спортом [1,2]. Не выявленная или не верно интерпретированная на начальном этапе кардиологическая патология, в будущем может обернуться необратимыми изменениями, которые в свою очередь, негативно отражаются на спортивных результатах, а после окончания профессиональной карьеры существенно снижают уровень здоровья и качества жизни экс-спортсменов [4].…”
unclassified